LEGAL PROTECTION OF WITNESSES TO OBTAIN ADVOCATE ASSISTANCE IN THE INVESTIGATION PROCESS - nggau, yonasius (Universitas Islam Lamongan, 2023)
The development of the times has made the dynamics of law in Indonesia follow suit, so that legal products are truly useful, provide certainty and justice. This makes regulations outside the Criminal Procedure Code and regulations from the Chief of Police appear to respond to all changes in legal dynamics that develop in society. As is the case with regard to legal protection for witnesses to obtain advocate assistance during the investigation process. This research was conducted using a normative juridical approach with the aim of getting an overview and explanation of whether a witness must be accompanied by an advocate at the Investigation stage as well as legal protection for witnesses at the investigative stage in criminal proceedings. The Investigative Process, the aim is none other than to protect the rights of witnesses. So that it is necessary to make changes to the criminal procedural code that are more modern according to the times and provide a sense of justice for society and protection of human rights.Â Keywords: Advocates, Legal Assistance, Witnesses, Investigations.Â